Three-dimensional sonographic measurement of blood volume flow in the umbilical cord - Pinter, Stephen Z; Rubin, Jonathan M; Kripfgans, Oliver D; Treadwell, Marjorie C; Romero, Vivian C; Richards, Michael S; Zhang, Man; Hall, Anne L; Fowlkes, J Brian (Journal of ultrasound in medicine, 2012)
Three-dimensional (3D) umbilical cord blood volume flow measurement with the intention of providing a straightforward, consistent, and accurate method that overcomes the limitations associated with traditional pulsed wave Doppler flow measurement and provides a means by which to recognize and manage at-risk pregnancies. The first study involved 3D sonographic volume flow measurements in 7 healthy ewes whose pregnancies ranged from 18 to 19 weeks' gestation (7 singletons). Sonographic umbilical arterial and venous flow measurements from each fetus were compared to the corresponding average measured arterial/venous flow to assess the feasibility of measurement in a static vessel. A second complementary study involved 3D sonographic volume flow measurements in 7 healthy women whose pregnancies ranged from 17.9 to 36.3 weeks' gestation (6 singletons and 1 twin). Umbilical venous flow measurements were compared to similar flow measurements reported in the literature. Pregnancy outcomes were abstracted from the medical records of the recruited patients. In the fetal sheep model, arterial/venous flow comparisons yielded errors of 10% or less for 8 of the 9 measurements. In the clinical study, venous flow measurements showed agreement with the literature over a range of gestational ages. Two of the 7 patients in the clinical study had lower flow than anticipated for gestational age; one had a subsequent diagnosis of intrauterine growth restriction, and the other had preeclampsia. Accurate measurement of umbilical blood volume flow can be performed with relative ease in both the sheep model and in humans using the proposed 3D sonographic flow measurement technique. Results encourage further development of the method as a means for diagnosis and identification of at-risk pregnancies.